Math Problem Statement
¬(¬p∨r)→(q→p),q→(p∨r)
Solution
Let's simplify and analyze the given logical expression step by step. The expression is:
¬(¬p ∨ r) → (q → p), q → (p ∨ r)
Step 1: Break down the components
Part 1: ¬(¬p ∨ r) → (q → p)
-
¬(¬p ∨ r): Using De Morgan's law:
¬(¬p ∨ r) ≡ ¬¬p ∧ ¬r ≡ p ∧ ¬r. -
q → p: This can be rewritten as ¬q ∨ p (implication equivalence).
So, the first part becomes: (p ∧ ¬r) → (¬q ∨ p).
Using implication equivalence again: (p ∧ ¬r) → (¬q ∨ p) ≡ ¬(p ∧ ¬r) ∨ (¬q ∨ p).
Simplify ¬(p ∧ ¬r):
¬(p ∧ ¬r) ≡ ¬p ∨ r.
Thus, the first part simplifies to: (¬p ∨ r) ∨ (¬q ∨ p).
Reorganize terms: ¬q ∨ p ∨ r.
Part 2: q → (p ∨ r)
Rewrite q → (p ∨ r) as: ¬q ∨ (p ∨ r).
Step 2: Combine the two parts
The full expression is: (¬q ∨ p ∨ r) ∧ (¬q ∨ (p ∨ r)).
Step 3: Simplify further
The second part, ¬q ∨ (p ∨ r), already overlaps with the first part, so the entire expression can be written as: ¬q ∨ p ∨ r.
Final Simplified Expression:
¬q ∨ p ∨ r
Would you like further explanation, examples, or details? Here are some related questions to deepen your understanding:
- What are De Morgan's laws, and how do they help in logical expressions?
- How does implication equivalence (p → q ≡ ¬p ∨ q) work in logical simplifications?
- How do you convert a compound logical expression into conjunctive or disjunctive normal form?
- What is the difference between logical validity and satisfiability?
- How can truth tables be used to verify logical equivalences?
Tip: Always apply De Morgan's laws and implication equivalences first when simplifying logical expressions. It makes subsequent steps easier.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Propositional Logic
Logical Equivalence
Implication
De Morgan's Laws
Formulas
Implication equivalence: p → q ≡ ¬p ∨ q
De Morgan's Laws: ¬(p ∨ q) ≡ ¬p ∧ ¬q and ¬(p ∧ q) ≡ ¬p ∨ ¬q
Theorems
De Morgan's Laws
Logical Equivalence Theorem
Suitable Grade Level
Grades 11-12 or Introductory College
Related Recommendation
Logical Equivalence of ∼[(p ∨ r) → ∼(p ∨ q)] Explained
Simplifying the Logical Expression (q → p) ∧ ¬(r ∧ q) Using Logical Equivalences
Logical Expression Simplification: ¬(q ⇒ ¬p) ⇒ (¬p ∨ q)
Logical Equivalence Proof: ¬p → (q → r) vs. q → (p ∨ r)
Analyzing Logical Expressions: (p ∨ q) → r and ~(q ∧ r) ↔ (p ∧ q)